Risk Assessment Based on Factor-Parametric Modeling - Rakhimov Oktiyabr Dostkabilovich; Yarasheva Manzura Yakhshiboy (EDUMALSYS Journal of Research in Education Management, 2026)
This article presents a scientific analysis of a factor-parametric modeling method that enables systematic risk assessment within labor protection management systems. It develops a logical basis for risk by constructing a factor-parametric framework for the “factors–object–protection–employee” system, conceptualized as a complex of fuzzy sets representing different configurations of factor and parameter types. At the core of this framework is the “v–f–r” model (“impact–mitigation–sensitivity”), which formalizes the interconnection between risk-inducing impacts (v), mitigating protection systems (f), and the sensitive object, i.e., the human (r). The condition for risk occurrence is evaluated by examining the balance and interaction among these components, thereby allowing the quantification and qualification of risk levels under varying combinations of impacts, protective measures, and human sensitivity. The proposed model contributes to the refinement of risk assessment methodologies by integrating factor-parametric modeling with fuzzy set representations, supporting more nuanced evaluation of occupational hazards and informing the design of more effective protection systems in labor protection management.